Subjective health assessments and active labor market participation of older men: evidence from a semiparametric binary choice model with nonadditive correlated individual-specific effects - Jürgen Maurer; Roger Klein; Francis Vella (Institute for the Study of Labor (IZA), 2007)
We use panel data from the US Health and Retirement Study 1992-2002 to estimate the effect of self-assessed health limitations on active labor market participation of men around retirement age. Self-assessments of health and functioning typically introduce an endogeneity bias when studying the effects of health on labor market participation. This results from justification bias, reflecting an individual's tendency to provide answers which justify his labor market activity, and individual-specific heterogeneity in providing subjective evaluations. We address both concerns. We propose a semiparametric binary choice procedure which incorporates potentially nonadditive correlated individual-specific effects. Our estimation strategy identifies and estimates the average partial effects of health and functioning on labor market participation. The results indicate that poor health and functioning play a major role in the labor market exit decisions of older men.
Keywords: I10; 360; Health; retirement; nonadditive correlated effects; semiparametric estimation; Ältere Arbeitskräfte; Erwerbstätigkeit; Gesundheit; Meinung; Präferenztheorie; USA